Numerical study on combustion efficiency of aluminum particles in solid rocket motor - WANG, Junlong; WANG, Ningfei; ZOU, Xiangrui; DONG, Wei; ZHOU, Yintao; XIE, Dingjiang; SHI, Baolu (Chinese journal of aeronautics, 2023)
The combustion of aluminum particles in solid rocket motor plays an important role in energy release of propellants. However, due to the limited residence time, aluminum particles may not be burned completely, thus hindering the improvement of specific impulse. This study aims to explore the characteristics of aluminum combustion efficiency and its influencing factors by experiments and numerical simulations, providing a guideline for engine performance improvement. As an input of simulation, the initial agglomerate size was measured by a high pressure system. Meanwhile, the size distribution of the particles in plume was measured by ground firing test to validate the numerical model. Then, a two-phase flow model coupling combustion of micro aluminum particle was developed, by which the detailed effects of particle size, detaching position and nozzle convergent section structure on aluminum combustion efficiency were explored. The results suggest that the average combustion temperature in the chamber drops with increasing initial particle size, while the maximum temperature increases slightly. In the tested motors, the aluminum particle burns completely as its diameter is smaller than 50 μm, and beyond 50 μm the combustion efficiency decreases obviously with the increase of initial size. As the diameter approaches to 75 μm, the combustion efficiency becomes more sensitive to particle size. The combustion efficiency of aluminum particle escaping from end-burning surfaces is significantly higher than that from internal burning surface, where the particle combustion efficiency decreases during approaching the convergent section. Furthermore, the combustion efficiency decreases slightly with increasing nozzle convergent section angle. And theoretically it is feasible to improve combustion efficiency of aluminum particles by designing the convergent profile of nozzle.